2017
DOI: 10.2106/jbjs.16.01200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Opioid Use on Total Knee Arthroplasty Outcomes

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 23 publications
(31 reference statements)
4
113
3
3
Order By: Relevance
“…Pain after primary TKA can be substantial and has been shown to increase continued opioid use and dependence in previously opioid-naïve [24] and opioid-experienced [25,26] M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 patients. Several studies have observed that tourniquets result in greater pain in the immediate postoperative period, [7][8][9][10][11][12] with two of those studies [7,12] showing increased analgesia consumption as a result and one showing no differences in analgesia consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Pain after primary TKA can be substantial and has been shown to increase continued opioid use and dependence in previously opioid-naïve [24] and opioid-experienced [25,26] M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 patients. Several studies have observed that tourniquets result in greater pain in the immediate postoperative period, [7][8][9][10][11][12] with two of those studies [7,12] showing increased analgesia consumption as a result and one showing no differences in analgesia consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with total hip arthroplasty patients, TKA patients were twice as likely to require refill opioid prescriptions and were prescribed a greater total morphine equivalent dose for a longer period of time postoperatively. Increasing evidence reveals that preoperative chronic use of opioids reduces the effect of pain relief postoperation, and increases postoperative opioid consumption in TKA patients. In addition, preoperative opioid use is associated with early revision, postoperative complications, worse clinical outcomes due to developed tolerance, and hyperalgesia, which can complicate recovery and rehabilitation.…”
Section: Preoperative Analgesic Regimensmentioning
confidence: 99%
“…In the adult reconstruction realm, prior research has demonstrated that patients prescribed preoperative opioids are at higher risk for perioperative morbidity, revision, and less satisfactory outcomes [4][5][6][7][8][9][10][11]. Much attention has also been paid to postoperative opioid regimens, and there has been increasing recognition that conservative postoperative prescription patterns of opioids can be both safe and effective [12].…”
Section: Introductionmentioning
confidence: 99%